ANALYSIS OF STUDENTS' IMPOSTOR PHENOMENON: SELF-ESTEEM AND ATYCHIPHOBIA IN MATHEMATICS LEARNING - Hayati, Nurul; Winarso, Widodo; Sofhya, Herlinda Nur'afwa (Universitas Labuhanbatu, 2024)
This study aims to analyze the impostor phenomenon of students and its relationship with self-esteem and atychiphobia in mathematics learning at SMA Negeri 1 Gegesik. This study uses a qualitative method with a case study design and criterion sampling technique. The subjects of the study were 143 grade XI students, where 8 students were identified as experiencing the impostor phenomenon with the criteria